As canções de câmara de Radamés Gnattali: diálogos composicionais e brasilidade - Luísa Vogt Cota (2022)
The thesis aims to understand the compositional dialogues and Brazilianness in Radamés Gnattali's songs for singing and piano. For this purpose, we sought to intertwine the composer's trajectory, his speeches and his chamber songs. The corpus chosen for this work is twenty songs (one of them a cycle of three songs) for singing and piano in handwritten scores, autograph handwritten as well as songs that were published. These scores were gathered during the research in collections, libraries as well as through contact with the composer's own collection, which is managed by his family. For work research and musical performance, these songs underwent an interpretive edition. The tripartite model of musical semiology, by Jean Molino, developed by Jean-Jacques Nattiez brought to the discussion of the thesis the relationship between author, work and performer for the interpretation of Radamés Gnattali's chamber songs. The theoretical framework in Mikhail Bakhtin enabled us to elucidate the issue of Radamés Gnattali's authorship as well as the dialogic relations of the composer's utterances, of his experiences, of the historical aspects of his time, of the poets who were partners in his songs. From the Bakhtinian perspective, we can see the reflection of the contexts lived by Gnattali in his songs, but also the creation of the composer about situations of the society in which he lived. There is a principle of alterity, in the sense of reflecting, but also refracting, musical meanings through their songs. The Brazilianness can be identified in the songs not only through characteristics of national music brought by modernist thought, such as rhythms and melodies existing in Brazilian popular music, and poems that refer to Brazil, but also through a more plural and more connected with the professional reality of Radamés Gnattali..The songs make it possible to reflect on the composer's trajectory and on his deviations – what goes beyond the idea of linearity and welldefined concepts. These reflections also allowed the performer the ability to create images and choose sounds and interpretations for the performance of Radamés Gnattali's chamber song, as well as establish dialogues with the composer. Gnattali's compositional forms allow re-readings and resignifications of her chamber songs for contemporary times.